2019
DOI: 10.1515/med-2019-0068
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in the elderly patient: the role of neo-adjuvant therapy

Abstract: AbstractBackgroundNeoadjuvant chemoradiotherapy has a significant role in downstaging cancer. It improves the local control of the disease and can make conservative resection of rectal cancer possible.MethodsWe enrolled 114 patients with subperitoneal rectal cancer who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Correspondingly, the number of older adults who are cancer patients requiring cancer care will only continue to increase [ 2 ]. That said, cancer care in the current era is increasing in complexity, with newer and better treatment options in aspects of care such as surgery, nutritional needs, nonsurgical treatment, wound care, and cancer surveillance [ 3 ]. Despite the amazing speed of technological adoption across different aspects of health care which are purportedly patient-centric (ie, bringing the service to the patients), care for patients with cancer remains very hospital-centric—the number of required visits to the hospital remains considerable for every patient.…”
Section: Introductionmentioning
confidence: 99%
“…Correspondingly, the number of older adults who are cancer patients requiring cancer care will only continue to increase [ 2 ]. That said, cancer care in the current era is increasing in complexity, with newer and better treatment options in aspects of care such as surgery, nutritional needs, nonsurgical treatment, wound care, and cancer surveillance [ 3 ]. Despite the amazing speed of technological adoption across different aspects of health care which are purportedly patient-centric (ie, bringing the service to the patients), care for patients with cancer remains very hospital-centric—the number of required visits to the hospital remains considerable for every patient.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients in this study had advanced tumor at preoperative staging (stage II or III), and after MDT evaluation a total of 23 patients (30.2%) underwent neoadjuvant therapy. Dodaro et al reported that better outcomes of neoadjuvant therapy can be achieved when this treatment is associated with a correct surgical technique “total mesorectal excision” (TME) [ 37 ]. Since many trials demonstrated that neoadjuvant therapy is associated with a decrease in local recurrence rates and an increase in the OS in all patients regardless of age [ 38 ], previous studies have examined the relation between elderly patients and local advanced rectal cancer [ 39 , 40 ], a subanalysis focusing in pTNM stage II and III was carried out to comprehend the role of this patients in terms of CSS and CRR at 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Undergoing an organ transplant can save lives, but it can also increase the risk of cancer [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Among patients who have undergone a solid organ transplant, the risk of getting cancer is 50% [ 79 ] ( Table 1 ).…”
Section: Transplantation and Risk Of Cancermentioning
confidence: 99%